2018
DOI: 10.1161/atvbaha.118.310940
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility Group Box 1 From Hypoxic Trophoblasts Promotes Endothelial Microparticle Production and Thrombophilia in Preeclampsia

Abstract: Our results indicate that placental hypoxia-induced HMGB1 expression and release from trophoblasts are important mechanism underlying increased circulating endothelial microparticles and thrombophilia in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 55 publications
2
31
0
1
Order By: Relevance
“…As a late inflammatory factor, HMGB1 is considered to be closely related to a variety of inflammatory diseases [ 7 , 8 ]. Recently, HMGB1 was found to be highly expressed in the placenta of PE women [ 9 , 10 ]. Placental hypoxia can promote the expression and release of HMGB1 from trophoblasts [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a late inflammatory factor, HMGB1 is considered to be closely related to a variety of inflammatory diseases [ 7 , 8 ]. Recently, HMGB1 was found to be highly expressed in the placenta of PE women [ 9 , 10 ]. Placental hypoxia can promote the expression and release of HMGB1 from trophoblasts [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…After damage of pathogenic factors, HMGB1 interacts with receptor for advanced glycation end-products and Toll-like receptors through active and passive release, causing the release of inflammatory mediators and stimulating the immune inflammatory response of the body [ 7 , 8 ]. It had been reported that placental hypoxia induced the expression and release of HMGB1 from trophoblasts [ 9 ]. Accumulating reports presented high levels of placental HMGB1 in women with PE [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the identication of water inrush in the coal mine, the traditional methods are mostly based on hydrochemistry, 9 through which we obtain pH, ion concentration, conductivity and other parameters to establish the classication model of mine water inrush. 10 However, hydrochemical methods have some limitations such as being time-consuming 11 and requiring specialized instruments and skilled operators, which restrict their applications in online warning of mine water inrush. To overcome these shortcomings, great focus has been put on developing fast, online and reliable methods for the identication of mine water inrush.…”
Section: Introductionsmentioning
confidence: 99%